2012
DOI: 10.4236/jbnb.2012.32024
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Dextrin Nanogel as Curcumin Delivery System

Abstract: Curcumin is a natural polyphenol with anti-oxidative, anti-inflammatory and anti-cancer properties. Its therapeutic potential is substantially hindered by the rather low water solubility and bioavailability, hence the need for suitable carriers. In this study, we show that self-assembled nanogels obtained from hydrophobically modified dextrin are effective curcumin nanocarriers. The stability and loading efficiency of curcumin-loaded nanogel depends on the nanogel/curcumin ratio. Higher stability of the formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Gonçalves et al . designed a nanogel formulation of curcumin having average size of 74 nm by loading curcumin into the hydrophobic domains of dextrin nanogel dispersed in distilled water or PBS after which the curcumin loading efficiency in the nanogel was analysed spectrophotometrically . Human cervical cancer cells (HeLa cells) were used to assay the biological activity of curcumin in the nanogel formulation.…”
Section: Nanoformulations Of Curcumin and Its Implications In Variousmentioning
confidence: 99%
“…Gonçalves et al . designed a nanogel formulation of curcumin having average size of 74 nm by loading curcumin into the hydrophobic domains of dextrin nanogel dispersed in distilled water or PBS after which the curcumin loading efficiency in the nanogel was analysed spectrophotometrically . Human cervical cancer cells (HeLa cells) were used to assay the biological activity of curcumin in the nanogel formulation.…”
Section: Nanoformulations Of Curcumin and Its Implications In Variousmentioning
confidence: 99%
“…Dextrin can be used as encapsulating agent of ethanol extract from Rhaphidophora pinnata leaves. 12 In nanoparticle formulations, the percentage of binder (arabic gum: dextrin) concentration used has a ratio of 1:0.5; 1:1, 75; 1:3; and 1:4.25 (data not shown). The best result obtained was a mixture of arabic gum and dextrin with a ratio of 1:0.5 which was easy to be granulated, dried, and milled to turn into nanoparticle powder.…”
Section: Discussionmentioning
confidence: 99%
“…The developed system was found to be favorable for pH-sensitive controlled delivery of curcumin and for cytotoxicity against human cervical cancer cell lines. Furthermore, Gonçalves et al [154,155] prepared a self-assembled nanogel obtained from hydrophobically modified dextrin as an effective curcumin nanocarrier. The in vitro release studies indicated the dextrin nanogel as a suitable carrier for the effective controlled release of curcumin.…”
Section: Herbal Drug Delivery Systems Against Cervical Cancermentioning
confidence: 99%